2018
DOI: 10.15403/jgld.2014.1121.274.yrs
|View full text |Cite
|
Sign up to set email alerts
|

Years of Life Lost due to Diseases of the Digestive System in Poland in 2000-2014

Abstract: Background & Aims: Diseases of the digestive system substantially contribute to premature mortality of the Polish population. Years of Life Lost (YLLs) are more and more commonly used in order to evaluate social and economic aspects of these deaths. The aim of the study was to analyse YLLs due to diseases of the digestive system in Poland between 2000-2014.Methods: The study material included a database which contained information gathered from 5,601,568 death certificates of Poles who died between 2000-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
1
1
Order By: Relevance
“…In our study, we observed that alcoholic liver disease (K70) was responsible for 31% of deaths in this group of causes in 2020, while fibrosis and cirrhosis (K74), largely caused by alcohol consumption, accounted for a further 12% of deaths due to digestive diseases. These values were slightly higher than in previous years ( 23 ).…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, we observed that alcoholic liver disease (K70) was responsible for 31% of deaths in this group of causes in 2020, while fibrosis and cirrhosis (K74), largely caused by alcohol consumption, accounted for a further 12% of deaths due to digestive diseases. These values were slightly higher than in previous years ( 23 ).…”
Section: Discussioncontrasting
confidence: 66%
“…W wielu badaniach wykazano, że mężczyźni tracą znacznie więcej lat życia na skutek przedwczesnych zgonów niż kobiety. Wyższe wartości mierników SEYLLp (per living person) w subpopulacji mężczyzn w porównaniu z kobietami odnotowywane są niemal w każdej klasie, grupie czy kategorii przyczyn zgonów [15][16][17][18]. W 2014 r. w Polsce najwięcej lat życia utracono na skutek chorób układu krążenia (721,4 na 10 000 mężczyzn i 475,6 na 10 000 kobiet), nowotworów złośliwych (odpowiednio, 575,5 i 418,3), niezamierzonych urazów (202,2 i 46,8), zamierzonych urazów (114,6 i 16,3) oraz chorób układu trawiennego (120,2 i 58,3) [19].…”
Section: Materiał I Metodyunclassified
“…The most important causes of deaths and lost years of life in Poland include cardiovascular diseases, malignant neoplasms, external causes, respiratory diseases and diseases of the digestive system 6 7. The latter group is dominated by diseases related to excessive use of alcohol, that is, alcoholic liver disease, fibrosis and cirrhosis of the liver as well as acute pancreatitis 8. In view of the increasing per capita alcohol consumption in Poland, along with the growth of other unhealthy behaviours related to the Westernisation, further analyses of the influence of socioeconomic variables on mortality due to digestive diseases are required 9 10.…”
Section: Introductionmentioning
confidence: 99%